An Economic Analysis of Women Domestic Workers in Namakkal District of Tamil Nadu - Parvathi, Dr. S. (International Journal of Advanced Science and Technology, 2020)
In India, women have few options for salaried work. In that few options domestic work is most important paid work for women. Many of the unorganised women workers come from weaker sections of the society. Most of the women workers migrant to city from rural areas. Most of the children and women are engaged in this work. They are most vulnerable to abuse. Many are at risk of extreme abuse. Domestic workers are not considered as workers. Their working conditions are remaining unregulated. Their employment condition is considered not fit for the general framework of existing employment laws. This is because most of the work done by them is usually undetectable. This type of workers excluded from National Labour Codes, No benefits of work contracts, social security, job security, medical facilities, wage increment, paid leave etc.,